Trust and artificial intelligence : development and application of AI technology - Paliszkiewicz, Joanna Olga; Gołuchowski, Jerzy (Routledge, 2025)
"Trust and Artificial Intelligence: Development and Application of AI Technology explores the crucial role of trust in the development and application of artificial intelligence (AI) technology. The book discusses the challenges and opportunities associated with building trust in AI systems and highlights the importance of transparency, accountability, and ethics in creating trustworthy AI. Drawing on the latest research and case studies, the book provides valuable insights and practical strategies for building trust in AI that can be applied by developers, policymakers, and end-users. It is a must-read for anyone interested in the intersection of technology and society and the future of artificial intelligence. Across its two distinct sections, the book delves deep into both theoretical frameworks and real-world applications. Section I, "Trust in Artificial Intelligence Technology," comprises twelve insightful chapters, each shedding light on different aspects of trust in AI. From ethical considerations and the credibility of AI systems to the intricacies of blockchain technology and digital therapists, the book offers a kaleidoscope of perspectives, showcasing how trust shapes and is shaped by AI advancements. Section II, "Trust in Artificial Intelligence Technology Applications," extends the discourse to practical implications and case studies. With twelve additional chapters, it scrutinizes the impact of AI on diverse sectors such as healthcare, agriculture, the labor market, and online shopping. It contemplates the trust dynamics in neural networks, public sector AI, and the burgeoning field of last-mile logistics. The book is more than just an academic text; it is a vital conversation starter in the ever-evolving discourse of AI. It challenges us to rethink our relationship with technology, underlining the critical role of trust in harnessing the full potential of AI for a better, more efficient, and ethically sound future"-- Provided by publisher.
Keywords: Artificial intelligence -- Social aspects.; Artificial intelligence -- Moral and ethical aspects.; Trust.; elektronické knihy; electronic books